Improving Communication Managerial Skill Among Women: Study On PT XYZ - Azka Mohammad; Harliantara, Harliantara; Nur’annafi Farni Syam Maella; Zulaikha, Zulaikha (SEAN Institute, 2024)
This case study explores the communication styles and managerial skills of women leaders at PT XYZ, a prominent Indonesian company. The research seeks to uncover the distinct strengths that women bring to management positions and invesorganizational empower and bolster their growth as leaders. Previous research has emphasized the positive communication skills that women frequently demonstrate in professional settings, including their ability to empathize, pay attention to details, and make inclusive decisions. The